Answer:
dy/dt = y ( 3 - y )
Step-by-step explanation:
Given data:
Determine an autonomous differential equation with the following properties
y = 0 and Y = 3
y' > 0 for 0 < y < 3
y' < 0 for -∞ < y < 0 and 3 < y < ∞
considering an autonomous differential equation
dy/dt = y ( 3 - y )
y = 0 and 3 represents equilibrium solutions
if 0 < y < 3 then y ( 3 - y ) > 0 for 0 < y < 3
hence : dy / dt = y' > 0 for 0 < y < 3
y ( 3 - y ) < 0 for -∞ < y < 0 and 3 < y < ∞
hence : dy / dt = y' < 0 for -∞ < y < 0 and 3 < y < ∞
this shows that the autonomous differential equation satisfies every condition hence the autonomous differential equation is :
dy/dt = y ( 3 - y )